Programme for Harmonization to the International Scale in Latin America for BCR-ABL1 quantification in CML patients: Findings and recommendations - Ruiz, María Sol (2020)
The quantitation of BCR-ABL1 mRNA is mandatory for chronic myeloid leukemia (CML) patients, and RT-qPCR is the most extensively used method in testing laboratories worldwide. Nevertheless, substantial variation in RT-qPCR results makes inter-laboratory comparability hard. To facilitate inter-laboratory comparative assessment, an international scale (IS) for BCR-ABL1 was proposed.The laboratory-specific conversion factor (CF) to the IS can be derived from the World Health Organization (WHO) genetic reference panel; however, this material is limited to the manufacturers to produce and calibrate secondary reference reagents. Therefore, we developed secondary reference calibrators, as lyophilized cellular material, aligned to the IS. Our purpose was both to re-evaluate the CF in 18 previously harmonized laboratories and to propagate the IS to new laboratories.Results Our field trial including 30 laboratories across Latin America showed that, after correction of raw BCR-ABL1/ABL1 ratios using CF, the relative mean bias was significantly reduced. We also performed a follow-up of participating laboratories by annually revalidating the process; our results support the need for continuous revalidation of CFs. All participating laboratories also received a calibrator to determine the limit of quantification (LOQ); 90% of them could reproducibly detect BCR-ABL1, indicating that these laboratories can report a consistent deep molecular response. In addition, aiming to investigate the variability of BCR-ABL1 measurements across different RNA inputs, we calculated PCR efficiency for each individual assay by using different amounts of RNA.Conclusions In conclusion, for the first time in Latin America, we have successfully organized a harmonization platform for BCR-ABL1 measurement that could be of immediate clinical benefit for monitoring the molecular response of patients in low-resource regions.